Word-formation in slavic languages: an onomasiological perspective (Philology, 2026)
The paper discusses methodological principles of evaluation word-formation systems in cross-linguistic research. The emphasis is on an onomasiological aspect of evaluation that is viewed as complementary with the semasiological evaluation. These two perspectives are indispensable for obtaining an objective picture of word-formation at various levels of generalization, including individual languages, language genera, language families and language areas. The paper illustrates the proposed method on a sample of Slavic languages.
Keywords: word-formation; onomasiology; structural richness; saturation value; Slavic languages